2019
DOI: 10.3389/fpsyt.2019.00208
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Cancer Patients

Abstract: Background: Being diagnosed with cancer and undergoing its treatment are associated with substantial distress that can cause long-lasting negative psychological outcomes. Resilience is an individual’s ability to maintain or restore relatively stable psychological and physical functioning when confronted with stressful life events and adversities. Posttraumatic growth (PTG) can be defined as positive life changes that result from major life crises or stressful events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
274
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(304 citation statements)
references
References 154 publications
(234 reference statements)
17
274
0
13
Order By: Relevance
“…We found that a higher level of perceived social support predicts higher resilience. This result is not surprising; previous studies confirm the buffering effect of social support [34,35]. Qualitative studies have indicated that social support, especially for patients with taboo diseases, such as vulvar neoplasia, is important to successfully cope with the situation.…”
Section: Discussionsupporting
confidence: 54%
“…We found that a higher level of perceived social support predicts higher resilience. This result is not surprising; previous studies confirm the buffering effect of social support [34,35]. Qualitative studies have indicated that social support, especially for patients with taboo diseases, such as vulvar neoplasia, is important to successfully cope with the situation.…”
Section: Discussionsupporting
confidence: 54%
“…La resiliencia correlaciona de forma positiva con el optimismo, la esperanza y el apoyo social percibido, y negativamente con la ansiedad y con el estrés percibido, en una población de pacientes con cáncer oral (Gao et al 2019 [43], Seiler and Jenewein (2019) [44]) mediante una indagación bibliográfica, restringida a Pub-Med, establecen que los factores biológicos, personales y en especial sociales aportan a la capacidad para recuperarse, en pacientes con cáncer. Además, encuentran que el PTG (crecimiento postraumático, es decir cambios positivos en la vida como producto de crisis vitales o eventos estresantes), es un factor relevante para adaptarse a esta condición, y construyen un modelo de resiliencia y PTG en pacientes con cáncer y sobrevivientes.…”
Section: Resultsunclassified
“…In this sense, depression and anxiety are mostly seen in cancer patients during their treatment [2]. Many cancer patients experience long-lasting negative psychological effects and perceive it as a traumatic illness due to its sudden onset and unclear nature after receiving diagnosis [3]. These emotional disorders can play a role in their lower quality of life and treatment compliance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since the treatment process (combinations of chemotherapy, radiotherapy, and surgery) is complex and problematic, patients' physical health, mental well-being, and relationships with loved ones may be adversely affected [1]. In contrast, as shown in studies, cancer and its treatment may be a chance for personal growth, positive life alterations, upgraded emotional and social well-being as a result of resilience [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation